2020
DOI: 10.1016/j.jhin.2020.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Unintended consequences of long-sleeved gowns in a critical care setting during the COVID-19 pandemic

Abstract: At the peak of the coronavirus disease 2019 (COVID-19) pandemic, hand hygiene audits indicated decreased compliance in a 12-bed critical care (CC) area with ventilated COVID-19 patients, where staff used personal protective equipment (PPE), including sessional use of long-sleeved gowns in accordance with the recommendations of Public Health England. There was also a cluster of three central venous catheter (CVC) infections along with increases in the number of patients from whom enteric Gram-negative bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…• In COVID-19 cohort units and ICUs, sessional use of PPE, e.g. longsleeved gowns that prevent effective hand hygiene [46] and gloves that may not be changed between patients [45] • Overcrowded facilities and possible staff shortages leading to low HCW-to-patient ratios [5] • Shortages of HCWs with appropriate IPC training [4] • Longer hospital stays for COVID-19 patients [5] • Traditional IPC efforts may be temporarily discontinued, including those targeting antibiotic-resistant bacteria, e.g. decreased frequency of screening for carriage of MDROs and difficulties in isolating or cohorting MDRO-positive patients [4,47] • Decreased laboratory capacity to detect AMR carriage, e.g.…”
Section: Type Of Factormentioning
confidence: 99%
“…• In COVID-19 cohort units and ICUs, sessional use of PPE, e.g. longsleeved gowns that prevent effective hand hygiene [46] and gloves that may not be changed between patients [45] • Overcrowded facilities and possible staff shortages leading to low HCW-to-patient ratios [5] • Shortages of HCWs with appropriate IPC training [4] • Longer hospital stays for COVID-19 patients [5] • Traditional IPC efforts may be temporarily discontinued, including those targeting antibiotic-resistant bacteria, e.g. decreased frequency of screening for carriage of MDROs and difficulties in isolating or cohorting MDRO-positive patients [4,47] • Decreased laboratory capacity to detect AMR carriage, e.g.…”
Section: Type Of Factormentioning
confidence: 99%
“…( 45 , 46 , 47 , 48 ) New research is also emerging on the type of gowns that best promote hand washing among HCWs. ( 49 ).…”
Section: Covid-19 and Infection Prevention And Controlmentioning
confidence: 99%
“…Donà et al recently highlighted the potential impact of COVID-19 on hospital transmission of MDROs [3]. Indeed, we are beginning to see reports fulfilling some of these authors' prophecies: Meda et al reported an increase in infections and environmental contamination with Gram-negative bacteria as a consequence of sessional use of long-sleeved gowns [4].…”
mentioning
confidence: 99%